Providing a Curriculum Model with an Entrepreneurial Approach for Top Talented Students in Iran - Rayeji, Ghorban; Azma, Fereydoon; Tajri, Tayebeh; Saeedi, Parviz (Iranian Journal of Educational Sociology, 2022)
Purpose: The present study was conducted with the aim of providing a curriculum model with an entrepreneurial approach for top talented students in Iran.Methodology: Research method in terms of purpose, was basic-applied. In terms of data type, it was mixed (qualitative) of exploratory type; and in terms of data collection time, it was cross-sectional and in terms of data collection method or the nature of the research, it was descriptive survey. The statistical population of the research in the qualitative section included all the heads of the Provincial Elite Foundation and the heads of the talented departments of the General Directorate of Education and the provinces and also 20% of the teachers implementing the Shahab project. Quantitatively, the statistical population includes junior high school students in gifted schools. The number of these students was 7000, using Cochran's formula, 364 people were selected. Sampling method was done through multi-stage cluster sampling. In the qualitative part of this study, the Delphi questionnaire based on CVR and CVI forms was used and in the quantitative part, the questionnaire was used to analyze the data. The validity and reliability of the instruments were evaluated and confirmed.Findings: The results showed that the curriculum with entrepreneurship approach for top talents including environmental components, economics, entrepreneurs, entrepreneurship, factors affecting the implementation of this approach in the curriculum, including components of support, teacher, system policies and influential factors of The curriculum was introduced with an entrepreneurial approach, including talent discovery, improving top talents and self-efficacy. Finally, a model was presented from two parts, quantitative and qualitative, which had a good fit.Conclusion: Recognizing talented students is one of the priorities of education and paying attention to the curriculum with an entrepreneurial approach to top talented students is an issue that has good consequences for students and society.